Pengaruh Kecerdasan Emosional dan Kemampuan Adaptasi terhadap Employee Engagement - Dhiya Ahadia Shafa; Arga Sutrisna; Barin Barlian (Penerbit Goodwood, 2022)
Purpose: This study aims to determine the emotional intelligence, adaptability, and employee engagement of non-manager employees at the Hotel Ramayana Tasikmalaya, to examine the effect of emotional intelligence, and adaptability simultaneously and partially on employee engagement of non-manager employees at the Hotel Ramayana Tasikmalaya. Methodology/approach: The research method used in this research is descriptive quantitative method with a census approach. Data collection techniques based on data sources in this study the author uses a questionnaire method. The analytical technique used in this study are validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation and determination coefficient analysis, F test, and t test. Results/findings: Emotional intelligence and adaptability simultaneously have a significant effect on employee engagement Hotel Ramayana Tasikmalaya; adaptability partially has a significant effect on employee engagement at Hotel Ramayana Tasikmalaya; emotional intelligence partially has a significant effect on employee engagement at Hotel Ramayana Tasikmalaya. Limitations: This study only assessed the variables of emotional intelligence, adaptability and employee involvement, and only non-manager workers who worked at the Ramayana Tasikmalaya Hotel, as well as the clear limited literacy on emotional intelligence and adaptability. Contribution: This study provides suggestions for Hotel Ramayana Tasikmalaya to provide rewards for outstanding employees, strengthen the kinship of fellow employees, provide training, and need to improve things that can affect the level of employee engagement.